The Impact of Occupation on Self-Rated Health: Cross-Sectional and Longitudinal Evidence from the Health and Retirement Survey - Gueorguieva, Ralitza (Oxford University Press, 2009)
BACKGROUND: The objective of this study is to estimate occupational differences in self-rated health, both in cross-section and over time, among older individuals. METHODS: We use hierarchical linear models to estimate self-reported health as a function of 8 occupational categories and key covariates. We examine self-reported health status over 7 waves (12 years) of the Health and Retirement Study. Our study sample includes 9,586 individuals with 55,389 observations. Longest occupation is used to measure the cumulative impact of occupation, address the potential for reverse causality, and allow the inclusion of all older individuals, including those no longer working. RESULTS: Significant baseline differences in self-reported health by occupation are found even after accounting for demographics, health habits, economic attributes, and employment characteristics. But contrary to our hypothesis, there is no support for significant differences in slopes of health trajectories even after accounting for dropout. CONCLUSIONS: Our findings suggest that occupation-related differences found at baseline are durable and persist as individuals age.